Determinación de parámetros normales de hemoglobina, hematocrito y glucosa sanguínea en niños de ocho a doce años de la Escuela Eugenio Espejo de la Parroquia Puerto Bolívar - El Oro - Ecuador - Bejarano Vera, Darwin F. (2008)
The hemoglobina is the main chemical component of the hematíes and fulfills important functions as they are the one of transport in the process breathing, in the maintenance and regulation of the call balance acid-bases some of plasmáticas proteins along with.